Missing out on precious time: Extending paid parental leave for parents of babies admitted to neonatal intensive or special care units for prolonged periods. (27th November 2021) - Spittle, Alicia J; McKinnon, Clare; Huang, Li; Burnett, Alice; Cameron, Kate; Doyle, Lex W; Anderson, Peter; Baird, Marian; Colditz, Paul; Cruz, Melanie; Pussell, Kylie; Dalziel, Kim; et al.
Abstract : In Australia, approximately 18% of newborn babies are admitted to a neonatal intensive or special care nursery. While most babies admitted to a neonatal intensive or special care nursery are discharged home within a few weeks, around 6% of babies spend more than 2 weeks in hospital. For the parents of these babies, much of their leave entitlements (Australian Government Paid Parental Leave Scheme is up to18 weeks for the primary care giver and up to 2 weeks for partners) are used before their baby comes home from hospital. The time babies and parents spend together in the early developmental period, during the hospitalisation and when the baby is discharged home, is crucial for optimal child development and bonding. Yet care givers who have a baby admitted to neonatal intensive or special care for extended periods are not currently entitled to any extra parental leave payments in Australia. We recommend the Australian Paid Parental Leave Act is changed to allow primary carers access to 1 week of extra parental leave pay for every week in hospital (for babies admitted to hospital for more than 2 weeks), up to a maximum of 14 weeks. For fathers and partners of these babies, we recommend an additional 2 weeks of extra Dad and Partner Pay. The net cost, taking into account likely productivity benefits, would be less than 1.5% of the current cost of the scheme and would improve health and socio‐economic outcomes for the baby, family and society.